Socioeconomic and policy determinants of mobility during COVID-19: Evidence from Indonesian cities - Khoirunurrofik Khoirunurrofik; Faris Abdurrachman; Utomo Noor Rachmanto (Journal of Urban Management, 2022)
Government interventions to limit the spread of the COVID-19 disease have decreased mobility, which, in turn, impacts aggregate economic activity. Understanding mobility during the COVID-19 pandemic may serve as a proxy for understanding its economic impact. This study aims to examine the relationship between pre-existing socioeconomic factors and the economic impact of COVID-19 using aggregate mobility data, particularly from emerging economies with a dominance of informal workers within economic activities. This study will utilize the public mobility dataset to provide an exploratory picture of the socioeconomic and policy determinants of mobility during the pandemic, focusing on Indonesia. The exploratory analytical findings indicate that the impact of COVID-19 on the economy, as indicated by mobility data, is highly correlated with various prior socioeconomic determinants. Moreover, more prosperous and urbanized areas have a larger formal sector, employ more people in manufacturing and/or tourism, possess a more educated labor force, and are more digitally connected; they tend to experience more significant decreases in mobility. The study has provided lessons to developing countries with a vast informal sector size and the gap in access to digital technology to design a more effective, timely, and well-targeted policy response in dealing with the COVID-19 pandemic.
Keywords: H12; D70; I18; D80; 710; COVID-19; Economic; Government intervention; Mobility; Non-pharmaceutical interventions